Factors Affecting the Mission Development of the Faculty of Pharmacy, Mahasarakham University. - Dumkum, Kwansiri; InJun, Rungsun (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
This research aimed to 1) study the factors affecting the mission development of the Faculty of Pharmacy, Mahasarakham University, 2) study mission development level of the Faculty of Pharmacy, Mahasarakham University, 3) study the relationship between factors affecting the mission development and mission development level of the Faculty of Pharmacy, Mahasarakham University and, 4) study approaching methods in enhancing mission development of the Faculty of Pharmacy, Mahasarakham University. This study used mixed method research by using quantitative and qualitative study. Samples of the quantitative research were students of Faculty of Pharmacy, Mahasarakham University, totally 256 samples through the data collecting by questionnaires. Informants of the qualitative research were comprised with 1) representatives of Faculty of Pharmacy, totally 9 subjects, and 2) representatives of Student Faculty of Pharmacy, totally 9 subjects through the focus group discussion method. The research findings were (1) Factors affecting the mission development of the Faculty of Pharmacy, in overall, was found in high level, which may arranged the factors as follows: (1.1) Faculty policy factor, (1.2) Technology factor, (1.3) Working approach of executive factor, (1.4) Student potential factor, (1.5) Resource of learning management factor, and (1.6) Personnel potential factor (2) Mission development level of the Faculty of Pharmacy, in overall, was found in high level, which may arranged the aspects as follows: (2.1) Producing graduates aspect, (2.2) Pharmaceutical research aspect, (2.3) Community health service aspect, and (2.4) Pharmaceutical vocation preservation aspect (3) The results of the correlation coefficient analysis found that factors affecting the mission development had statistically significant correlation with the mission development level of the Faculty of Pharmacy at .05 level, and (4) approaching methods in enhancing mission development of the Faculty of Pharmacy, can be concluded as follows: (4.1) Faculty policy should be clear and should urge in any working aspect to be in accordance with the mission, (4.2) Should encourage in technology application for learning, (4.3) Should focus on students security by developing a safe laboratory and conducting some technology to be more effective in producing medicines, and (4.4) Should contribute a budget to students for organizing public events or activities. Article history: Received 17 August 2019 Revised 23 November 2019 Accepted 28 November 2019 SIMILARITY INDEX = 1.17%